Microanatomical Studies on the Broncho-pulmonary Segments of Lungs in Domestic Pig (Sus scrofa domesticus) - Srujana, G.; Pramod, K. D.; Rajendranath, N.; Madhava, R. T.; Archana, K. (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted from December, 2020 to May, 2021 in the Department of Veterinary Anatomy, College of Veterinary Science, Rajendranagar, Hyderabad, India to provide a thorough description of the histological characteristics of the broncho-pulmonary segments of domestic pig lungs, given the structural similarities between human and pig lungs and the significance of this species as an experimental model for biomedical research. A typical broncho-pulmonary segment was composed of the following histological structures: segmental bronchi, primary, secondary, and tertiary bronchioles and their branches, all of which terminated in an alveolar duct or a cluster of alveoli. Each broncho-pulmonary segment was accompanied by a matching artery to the tiniest divisions of the bronchial tree. Lamina mucosa, sub-mucosa, and outer adventitia were the three layers of secondary (lobar) bronchi. Mucosal layer was lined by pseudo-stratified ciliated columnar epithelium; the sub-mucosal layer was made up of a hyaline cartilage layer and a stretch of sub-mucosal glands and blood vessels. Segmental bronchi epithelium was simple columnar, stratified cuboidal while cuboidal in terminal bronchioles. The terminal bronchioles had a folded mucosa, formed of small strands of collagen and smooth muscle fibres. Terminal bronchioles were linked to alveolar ducts, which in turn were linked to a spate of alveoli with squamous epithelium.